PENGARUH PEMBELAJARAN BERBASIS MASALAH LINGKUNGAN TERHADAP BERPIKIR KRITIS SISWA PADA MATA PELAJARAN GEOGRAFI KELAS XI SMA NEGERI 1 LEMBANG - Marsudi, - (2011)
This thesis is motivated that socal Studies is one of the subjects who reviewed the series of events, facts, concepts, and generalizations relating to social issues, Geography as one of the subjects of Social Sciences to study the interaction between humans and the environment. This study focuses on the development of Problem Based Learning in Geography subject in class XI for improve the competence of student in critical thinking and logical, capable of problems solving, and have skills in social life, so also increase the competence of students on the importance of preserving the environment.Problem-based learning involves students in active learning, collaborative, student-centered, which develops problem-solving skills and independent learning skills. The method of this study was quasi experimental design with pretest-posttest nonequivalen groups.Subjects in this study were grade XI 2 and XI 3 for the second semester of the school year 2010/2011. The instrument which is used was a test of critical thinking and guidance observation.The test hypothesis with the statistical analysis with SPSS version 17. The results showed that there are significant differences between the pretest to posttest critical thinking in class using problem-based learning, observations indicated that all the indicators show an increase in critical thinking, from the nine indicators, the highest score is the indicator of "problems solving", got a score of 55, whereas the lowest score is the indicator of "defining the term and definition to determine if needed" , got a score of 43.There are also significant differences between the pretest to posttest critical thinking in classes that do not use problem-based learning, and there are significant differences between the results of critical thinking skills students used problem-based learning with that without treatment.It can be concluded that problem-based learning environment provides a positive influence on students' critical thinking skills.The recommendations can be submitted: a) In order for this problem-based learning to walk with the optimum can be done by team teaching, b) The effort to increase students' critical thinking skills, for further research, the results of this study can be compared with other learning models, especially on the subjects of Geography in Senior High School (SMA)